PENGARUH TINGKAT LITERASI DIGITAL TERHADAP PENGELOLAAN PRIVASI KOMUNIKASI REMAJA DALAM PEER GROUP: Survei Pada Siswa MA Usb Filial MAN Batam - Nuria Milga Yusuf (2022)
This study aims to determine how much influence the level of digital literacy has on the management of adolescent communication privacy in peer groups at MA Usb Filial MAN Batam students and examines the relationship between digital literacy levels and the management of adolescent communication privacy in peer groups using communication privacy management theory (CPM). The method used is quantitative, with the type of explanation. The sampling technique is probability sampling using proportionate stratified random sampling. Researchers used a survey technique by distributing questionnaires to 86 respondents. The final result of this research is that the relationship between digital literacy level and communication privacy management lies in a fairly weak category. Researchers get the results that the level of Digital Literacy has a positive effect and contributes 36.30% to Communication Privacy management. This research is in line with the theory of communication privacy management (CPM) where digital literacy is a means of managing youth communication privacy in peer groups. Keywords: Interpersonal communication, digital literacy, peer group, communication privacy management, youth